Reimagining Judicial Reasoning: The Legal Implications of Neurotechnology in Child Custody Adjudication - Aten Kuswendi; Artiyanto Artiyanto; Septia Novarisa (IJoIS: Indonesian Journal of Islamic Studies, 2026)
This study examines the juridical implications of neurotechnology in judicial reasoning within child custody adjudication. While existing scholarship in neurolaw has largely focused on criminal justice, limited attention has been given to its application in family law, particularly from a doctrinal and evidentiary perspective. Addressing this gap, the study employs a normative legal research approach to analyse the evidentiary status of neurotechnology and its role in supporting judicial decision-making. Child custody adjudication, guided by the best interests of the child, often relies on interpretative assessments that may generate subjectivity and inconsistency. Neurotechnologies such as functional magnetic resonance imaging (fMRI) and electroencephalography (EEG) offer potential empirical insights into psychological and emotional conditions relevant to parental capacity. However, the findings demonstrate that although neurotechnology may be classified as expert scientific evidence, its admissibility remains contingent upon established standards of relevance, reliability, and scientific validity. The study further identifies a critical epistemic gap between neuroscientific data and legally meaningful conclusions, indicating that neurotechnology does not eliminate subjectivity but rather reconfigures it through expert interpretation. Accordingly, this research argues that neurotechnology must be positioned as a supplementary evidentiary tool rather than a determinative basis for judicial decisions. This study contributes theoretically by extending neurolaw into the domain of family law and normatively by proposing a regulatory framework that emphasises procedural safeguards, protection of individual rights, and the preservation of judicial discretion.